Green economy and inclusive communities: Achieving harmony between humans and nature - Salman, Muhammad Iswari A (Institute for Advanced Science Social, and Sustainable Future, 2025)
Background: This study aims to explore and analyze the implementation of a green economy in the context of sustainable development, with a focus on the development of an inclusive society. Methods: The approach used is a literature review with a descriptive-analytical method, involving various secondary sources, such as scientific journals, reports from international institutions, and government policies. Findings: The results show that the transition to a green economy requires the integration of sustainability principles in development policies at various levels. In addition to resource efficiency and carbon emission reduction, the green economy must also encompass social justice and protection for vulnerable groups. Key challenges in implementing a green economy include weak institutional capacity, resistance to policy changes, and financing gaps, particularly in developing countries. Furthermore, the importance of an interdisciplinary approach, collaboration between the public and private sectors, and community participation in decision-making are key factors in the success of the green transition. Novelty/Originality of this article: This study also highlights the importance of education and technological innovation to support sustainability and economic resilience. Overall, the findings provide valuable insights into the need for a fair and inclusive green economy as part of the sustainable development agenda.